(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
Pedagogical studies in the morphology of Malay language have long been conducted since the 19th century. In this regard, Boer (1951), is his grammatical work, has summarized the classification of the meaning of the suffix -an -an into three major groups. However, this work is hardly noticed by local researchers. Since the 1980s, the results of the analyses of the meaning of the suffix concerned have been presented in detail in Indonesia and Malaysia. The author has compared three Malay-language works, namely Asmah (2009), Harimurti (1996), and Nik Safiah et al. (2010). However, the various meanings of the suffixes concerned are not related to each other, and even the examples given are sometimes inconsistent. This article used a logical rearrangement of the classification of meaning and introduces four classifications of the meaning of the suffix -an -an along with basic mathematical ideas as their auxiliaries, namely: I. "set unit"; II. "similarity"; III. "something related with the process of action", and; IV. "the influence of tribal languages in Indonesia". With this classification, the relationship between the various meanings of the suffix -an -an could be clarified easily. The method used by this foreign researcher is the result of foreign students who are learning Malay language in order to ease the burden of memorization through dictionary and textbook grammar.